Corra Harris and the Divided Mind of the New South - Oglesby, Catherine (Book collections on Project MUSE., 2008)
"During her life, Corra Harris (1869-1935) was one of the most widely published and popular female writers in the United States. In addition to dozens of books, her work appeared frequently in major national publications such as Saturday Evening Post, Harper's, Good Housekeeping, and Ladies Home Journal. Critics have often dismissed her claim to prominence, choosing to view her as a writer of domestic fiction. At the same time, she was widely praised for her expressions of wit and candor. A Circuit Rider's Wife (1910) was Georgia's most celebrated novel for nearly three decades. Now little read and almost forgotten. Harris's life offers a fascinating glimpse into a world nearly unimaginable to us today."--Jacket.